Wellbeing in preschoolers. Important factors in creating educational patterns - Olivia Pisică (Journal of Education, Society & Multiculturalism, 2020)
The kindergarten influences the formation of the child’s personality through various methods and activities that include all socio-cultural categories. During this period the foundation of good communication, relationships with others, activities that will lead the child towards the beginning of his personality formation are laid. Micro-research aims to find out to what extent the activities in the family environment and the preschool are oriented towards the formation of healthy behavior with specific social integration notes, then the child will be assured active group / community integration by forming specific patterns of autonomy. In research paper we aim at achieving the following objectives: to identify how wellbeing process is understood by educators and parents by ensuring quality of life in terms of health, material status, access to education or quality social services; to highlight the physical, mental and cultural links between play, learning and physical and mental health in pre-school children through various types of games, activities and elements of creative stimulation; to create healthy opportunities and situations for the child’s behavior in the kindergarten and beyond, through creative, transferable activities. Data collection methods are: questionnaire, focus group.